Cactus: Chemical, nutraceutical composition and potential bio‐pharmacological properties. (6th October 2020) - Das, Gitishree; Lim, Kyung Jik; Tantengco, Ourlad Alzeus G.; Carag, Harold M.; Gonçalves, Sandra; Romano, Anabela; Das, Swagat Kumar; Coy‐Barrera, Ericsson; Shin, Han‐Seung; Gutiérrez‐Grijalva, Erick Paul; Heredia, J. Basilio; Patra, Jayanta Kumar
Abstract : Cactus species are plants that grow in the arid and semiarid regions of the world. They have long fascinated the attention of the scientific community due to their unusual biology. Cactus species are used for a variety of purposes, such as food, fodder, ornamental, and as medicinal plants. In the last regard, they have been used in traditional medicine for eras by the ancient people to cure several diseases. Recent scientific investigations suggest that cactus materials may be used as a source of naturally‐occurring products, such as mucilage, fiber, pigments, and antioxidants. For this reason, numerous species under this family are becoming endangered and extinct. This review provides an overview of the habitat, classification, phytochemistry, chemical constituents, extraction and isolation of bioactive compounds, nutritional and pharmacological potential with pre‐clinical and clinical studies of different Cactus species. Furthermore, conservation strategies for the ornamental and endangered species have also been discussed.